Work-Family Conflict And Job Stress And The Influence On Employee Turnover Intention In RSU Puri Asih Karawang District - Ais, Ropahal; Nadeak, Banuara (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The Puri Asih Hospital turnover intention increased from 2016 to 2018, peaking at 10% in 2016. The goal is to research how work-family conflict and stress affect female RSU Puri Asih Jatisari Karawang workers' turnover intention. The theory employed is Work-Family Conflict (X1) by Greenhaus & Beutell (1985), which comprises Time-, Strain-, and Behavior-based Conflict, and Job Stress (X2) by Handoko (2008), which includes ON- and OFF-Job Stress. Turnover Intention (Y) was examined using Mobley et al.'s (1978) theory of Thinking of Quitting, Searching for Alternatives, and Quitting. Associational descriptive quantitative research is used. The Slovin algorithm and purposive sampling were used to choose 58 of 140 married female RSU Puri Asih Jatisari Karawang workers. We use primary and secondary data. Data analysis was done using IBM SPSS version 23, including descriptive analysis, validity, reliability, correlation coefficient, multiple linear regression, partial (t), simultaneous (F), and coefficient of determination tests. Work-Family Conflict (X1) and Job Stress (X2) substantially affect Turnover Intention (Y), with an R2 value of 35.2%, whereas 64.8% is impacted by other factors.